2011
DOI: 10.1007/s00011-011-0400-z
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 protein attenuates cyclosporine-induced renal hemodynamics changes and macrophage infiltration in rats

Abstract: Background Cyclosporine (CsA) remains an important immunosuppressant for transplantation and for treatment of autoimmune diseases. The most troublesome side effect of CsA is renal injury. Acute CsA-induced nephrotoxicity is characterized by reduced renal blood flow (RBF) and glomerular filtration rate (GFR) due to afferent arteriole vasoconstriction. Annexin A1 (ANXA1) is a potent antiinflammatory protein with protective effect in renal ischemia/reperfusion injury. Here we study the effects of ANXA1 treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Studies presented evidence that nephrotoxicants could provoke an inflammatory response leading to organ injury [12,34]. The significantly elevated TNF-α reflects the degree of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies presented evidence that nephrotoxicants could provoke an inflammatory response leading to organ injury [12,34]. The significantly elevated TNF-α reflects the degree of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin-1, implicated in cell proliferation and differentiation, is characteristically associated with anti-inflammatory responses (45), mediated in part through inhibition of MAP kinases (46). In WT hTRPM7 cells, activation of annexin-1 as assessed by membrane translocation, was significantly increased by aldsoterone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous localization studies for AnxA1 have shown strong expression of the protein in renal epithelia and an increased abundance in response to renal injury (McKanna et al 1992, Araujo et al 2012, Ka et al 2014. These studies also suggested interstitial expres-sion of AnxA1, but its cellular source and function were unknown.…”
Section: Mergementioning
confidence: 94%